Supernatural Creatures in Arabic Literary Tradition - Al-Rawi, Ahmed (Taylor & Francis Group, 2023)
Cover – Half Title – Series Page – Title Page – Copyright Page – Table of Contents – Preface – Chapter 1 The ghoul – Chapter 2 The Rukh – Chapter 3 The dragon – Conclusion – Index.
Description based on publisher supplied metadata and other sources
Keywords: Arabic literature-History and criticism; Supernatural in literature; Ghouls and ogres in literature; Roc (Mythical bird)-In literature; Dragons in literature